Ketahanan pangan dan gizi pelaku Usaha Mikro, Kecil dan Menengah (UMKM) berbasis produk pangan lokal di Kecamatan Tirtayasa Kabupaten Serang - Widiati, Siti; Azkia, Lana Izzul (Jurnal Sosio Agribisnis, 2023)
Food security is the state of having individuals or groups with access to enough food and nutrition. Local food resources play a crucial role in meeting the dietary needs of the community. Abinisa's Small and Medium Enterprises (SMEs) are one of the producers of local food products in the city of Serang. Improving the economic status of SME operators can bolster the food security and nutrition of their households. The objective of this research is to analyze food security based on Food Expenditure Share (FES) and to assess food security and nutrition based on Energy Adequacy Ratio (EAR) and Protein Adequacy Ratio (PAR) among entrepreneurs in Abinisa's SMEs. This study is descriptive in nature, aiming to provide an overview of the conditions in the field. The data used in this research includes both primary and secondary sources. The research results indicate that the majority of households among SME operators fall into the category of being food secure, with an average Food Expenditure Share of less than 60 percent. Additionally, the levels of energy and protein adequacy in the households of entrepreneurs in Abinisa's SMEs average above 80 percent. Keywordsi: food Security; SME; local food products